2023
DOI: 10.1038/s41598-023-29706-6
|View full text |Cite|
|
Sign up to set email alerts
|

Regorafenib is suitable for advanced colorectal cancer patients who have previously received trifluridine/tipiracil plus bevacizumab

Abstract: Regorafenib is a standard salvage line therapy used for advanced colorectal cancer (CRC). Recently, trifluridine/tipiracil (TFTD) plus bevacizumab also showed promising efficacy as a salvage line therapy for advanced CRC. However, the efficacy and safety of regorafenib for patients with advanced CRC who have previously received TFTD plus bevacizumab is unclear. We retrospectively collected clinicopathologic data from patients with advanced CRC who received regorafenib after TFTD plus bevacizumab in multiple in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, because of differences among cases and the presence of several molecular subtypes, evaluating therapy alternatives is difficult, and in the setting of varying tolerance profiles against minor improvements in overall survival and progression-free survival, T and R are still regarded by some as clinically unimportant [ 25 , 26 , 27 , 28 ]. The best protocols for the administration of T and R in patients with advanced disease, the identification of subpopulations that might benefit from vital treatment with these drugs, and the identification of those subpopulations that might benefit from treatment with these drugs vs. the best supportive therapy alone are all questions that have yet to be resolved [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Furthermore, T and R have not been directly compared to one another, and it is uncertain which agent should be given first [ 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, because of differences among cases and the presence of several molecular subtypes, evaluating therapy alternatives is difficult, and in the setting of varying tolerance profiles against minor improvements in overall survival and progression-free survival, T and R are still regarded by some as clinically unimportant [ 25 , 26 , 27 , 28 ]. The best protocols for the administration of T and R in patients with advanced disease, the identification of subpopulations that might benefit from vital treatment with these drugs, and the identification of those subpopulations that might benefit from treatment with these drugs vs. the best supportive therapy alone are all questions that have yet to be resolved [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Furthermore, T and R have not been directly compared to one another, and it is uncertain which agent should be given first [ 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of metastatic CRC, regorafenib is clinically applied as a therapy for pre-treated patients with progressive disease after two phase 3 clinical trials (CORRECT and CONCUR studies) from 2013 and 2015 revealed significantly prolonged overall survival [182,183]. Notably, regorafenib also showed activity as a second-line therapy in patients with advanced CRC pre-treated with bevacizumab plus trifluridine/tipiracil [184]. Meanwhile, the dual RAF/VEGFR2 inhibitor RAF265 has undergone a first-in-human phase 1 clinical trial with melanoma patients.…”
Section: Clinical Trials Of Vegfr Inhibitors In Braf Mutant Cancersmentioning
confidence: 99%